Identifikasi Tantangan dan Strategi dalam Implementasi Kurikulum Merdeka pada Tingkat Sekolah Dasar - Ayu Ningsi; Sukiman Sukiman; Anggita Agustina; Minati Rina Hardiyana; Sholihah Ummi Nirmala (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The curriculum has become an integral part of the world of education. History has shown that there have been a series of curriculum changes that occurred in Indonesia. These curriculum changes are the result of an in-depth analysis carried out by policymakers. The change from the 2013 Curriculum to the Independent Curriculum is part of the Indonesian government's efforts to continue to improve and review the education system in the country. Therefore, this research aims to identify challenges in implementing the Independent Curriculum at the elementary school level. The importance of identifying each of these challenges is to develop appropriate and measurable strategies to support the successful implementation of the Independent Curriculum and improve the quality of learning at the elementary school level. This research is a literature study, researchers collected data from various literature sources that have been published in national and international journals which can be accessed online. Searches for scientific articles were carried out using search platforms such as Scopus and Scholar, researchers also applied interview techniques carried out at SDS Islam Madani Kayuagung as an additional data collection method, to strengthen and complement the information contained in literary sources. The results of the research show that there are problems in implementing the independent curriculum, especially at the elementary school level, where teachers experience difficulties in analyzing Learning Achievements, teachers do not master the use of technology so teachers face difficulties in preparing lesson plans, teachers experience difficulties in determining the type of assessment that is suitable for the objectives. learning to be achieved, especially when implementing project-based learning.